Sleep disorders during pregnancy - its prevalence, characteristic and neonatal implications - Sebastian Tomaszuk; Karolina Wąsik; Magda Wojtuś (Kazimierz Wielki University, 2024)
Introduction and purpose: Each phase of a woman's life, from childhood to menopause, may be associated with a variety of sleep disturbances. The pregnancy is particularly predisposed to develop sleep disorders such as insomnia, restless legs syndrome and sleep-disordered breathing, which require special management. This article reviews the most common sleep disturbances in pregnancy and discusses epidemiology, pathophysiology, maternal and fetal possible implications and therapeutic options in the pregnant population. Material and methods of research: The search was conducted using PubMed and Google Scholarship databases available to January 2024.  Results: Although the exact cause of previously mentioned diseases remains uncertain, the impact of hormonal changes, the body mass before pregnancy and weight gaining during gestation on their development is highlighted by researchers. Poor sleep in pregnancy may have negative outcomes for women as well as fetuses and influence the pregnancy course. These sleeping disorders may also contribute to development of other systemic diseases. The management of sleep disturbance in pregnant patients is challenging due to the risk of teratogenicity, pharmacokinetic changes and the dynamic nature of pregnancy, thus nonpharmacologic interventions should be preferred as safer than medications.  Conclusions: Sleep disturbances result in poorer quality of pregnant women's life and have negative impact on the condition of pregnancy. Thus, this theme should create the need for additional research on the possibilities of prevention and treatment strategies of sleep disorders in pregnant women.